The Effect of Combined External-Beam Radiotherapy and Brachytherapy on Local-Control and Wound Complications in Patients with High-Grade Soft-Tissue Sarcomas of the Extremity with Positive Microscopic Margin - Alektiar, K. M. (Institutional Knowledge at Singapore Management University, 1996)
A previously reported randomized trial from our institution demonstrated a local control advantage to adjuvant brachytherapy (BRT) for completely resected high grade soft tissue sarcoma (STS). In recent years, BRT boost has been combined with wide field external beam radiotherapy (EBRT) for selected patients in whom the margin(s) of resection was positive. This study evaluates the impact of BRT boost plus EBRT on local control in this subset of patients and on wound complication rates. Methods and Materials : Between January, 1987 and December, 1992, 105 adult patients with primary or locally recurrent high grade STS of the extremity were treated with wide local excision and BRT alone (87 patients ; dose : 45 Gy) or BRT plus EBRT (18 patients ; dose : 15-20 Gy BRT + 45-50 Gy EBRT). The margin(s) of resection was positive in 10 out of 18 patients in the BRT+EBRT group vs. 17 out of 87 patients in the BRT alone group. Wound complications were classified as major if they required further operative intervention ; moderate if there was purulent discharge, hematoma > 25 ml, wound separation > 2 cm, and persistent seroma requiring drainage ; or minor if less than moderate. Median follow-up was 22 months. Results : The overall 2-year actuarial local control rate was 86%. There was no difference in the 2-year actuarial local control rate between the BRT+EBRT group (90%) and the BRT alone group (82%) (p = 0.32). However, for patients with positive resection margins the use of BRT+EBRT produced better local control than BRT alone [9 out of 10 (90%) vs. 10 out of 17 (59%)]. This difference approached but did not reach statistical significance (p = 0.08). No difference was seen in patients with negative margins. There was no significant difference in the overall wound complication rate (26% BRT vs. 38% BRT+EBRT, p = 0.31) nor in the combined major and moderate wound complication rate (16% BRT vs. 27% BRT+EBRT, p = 0.39). Conclusion : Our preliminary data suggest a trend in favor of BRT boost + EBRT as the optimal adjuvant local strategy for STS with positive resection margins. There is no significant difference in the wound complication rate with either technique.